Manejo silvicultural de la especie Anaueria brasilienses kost (Añuje rumo) en la etapa inicial en vivero forestal de Puerto Almendras. San Juan -Maynas- Loreto. 2022 - Quinto Guillen, Frank Tomy (2023)
This research was carried out in the forestry nursery of the National University of the Peruvian Amazon, located in the city centre of Puerto Almendras, in San Juan de Miraflores District, Iquitos city, Loreto department, in order to determine the time that it can be preserved in its natural state, germination period, degree of survival and mortality of germinated seedlings. According to the obtained results, it can be indicated that the average weight of seeds of the species Anaueria brasilienses kost after seed collection is 0.69 kg and the weight after 60 days of drying in the open air is 0.45 kg. The number of seeds per kg after collection is 15 seeds and after drying in the open air it increases between 20 and 22 seeds per kilogram. The humidity percentage after 60 days reaches 35%. The germnation of scarified seeds of the species begins 50 days after sowing and ends at 61 days, the method of soaking in cold water begins at 53 days and ends at 62 days and the seeds without treatment begin their germination at 58 days and finish at 65 days. The germination percentage of the seeds was 92% for the scarification treatment, 80% for soaking in cold water and 64% for the seeds without treatment 5. The percentage of seed quality was 92%. The null hypothesis that all treatments are equal is approved as confirmed by the analysis of variance.